My mother cursed my name : a novel - Salgado Reyes, Anamely (Atria Books, 2024)
"Three generations of fiercely strong and stubborn Mexican American women face grief head-on as they attempt to shed generational trauma and discover the true meaning of home in this lyrical novel that features magical realism in the tradition of The Inheritance of Orquídea Divina and The House of the Spirits. For generations, the Olivares women have sought to control their daughters' destinies, starting with their names. In life, Olvido constantly clashed with her carefree daughter. Then teenage Angustias discovered she was pregnant and left her mother's home in search of her own. Ten years later, Felicitas finally meets her estranged grandmother and is terribly disappointed when Olvido is nothing like a grandmother should be. She is strict, cold, and...dead. Now, Olvido is convinced the only way her spirit will cross over is if she resolves her unfinished business-to make sure Angustias is in a better place regarding family, job, husband, and God, but maybe not in that order-and Felicitas is the only person who can see or hear her. Heartbroken about her mother's passing and desperate to put Olvido's tiny Texas home in her rearview mirror as quickly as possible, Angustias doesn't understand why suddenly everyone in town seems to be conspiring to set her up with every eligible bachelor in town, offer her jobs, and invite her and Felicitas to church every Sunday. As Olvido attempts to puppeteer her granddaughter to "fix" Angustias's life from beyond the grave, Angustias tries desperately to find a better place for Felicitas, and Felicitas struggles to keep her ability to see the dead a secret from Angustias, all three Olivares girls are forced to learn how to actually listen to one another, to work to overcome generations' worth of well-intentioned mistakes and learn the true definition of home." —publisher.